THE EFFECT OF SOYBEAN FLOUR SUBSTITUTION WITH PALM KERNEL MEAL IN FEED ON GROWTH AND SURVIVAL OF SANGKURIANG CATFISH (Clarias sp.) - Sarmila, Sarmila; Pratama, Wahyu Wira; Shidiq, M. Faiq Ash (Universitas Mataram, 2025)
Palm kernel meal is considered very potential to be used as fish feed because it contains 15.43% crude protein. The problem by aquaculture is the imbalance in income obtained compared to production costs that have been incurred. This is because farmers depend on manufactured feed so that the price of commercial feed issued is high. The purpose of this study was to analyze the effect of different soybean meal and palm kernel meal feed substitutions on the growth and survival of catfish (Clarias sp). The study used a Completely Randomized Design with 3 treatments and 4 repetitions, consisted of three main treatments, namely: the first treatment (P1) feed based on a ratio of 80% soybean meal with 20% palm kernel meal and the second treatment (P2) feed based on 70% soybean meal and 30% palm kernel meal and (P3) feed based on 60% soybean meal and 40% palm kernel meal...The highest Weight gain value was found in P1 at 71.3 gr, followed by P2 at 51.5 gr, and P3 at 47.6 gr. The results showed that the highest RGR value was found in treatment P1 at 0.3% followed by treatments P2 and P3 at 0.2%. The best Feed Covertion Ratio (FCR) was found in treatment P1 at 4.31, followed by treatment P2 at 5.85 and treatment P3 at 6.22. The highest SR in treatment was found in treatment P1 at 91.7% followed by P2 and P3 at 90%.